La comprensión lectora y su incidencia en el rendimiento académico de los estudiantes del subnivel de educación básica media - Oña Chicaiza, Angel Marcelo (2017)
This research has the purpose about reading comprehension and its impact on academic performance from "Enrique Izurieta" students, a diagnosis will be useful contribution to future research in an appropriate way. Determining the lack of reading comprehension within the students, for it is applied a deductive, inductive and dialectical methodology; techniques, interview with its question guide instrument, survey with its instrument the questionnaire were used too; would route to establish the deficit of the reading comprehension that is a social problem. This research work generated a practical contribution establish important data regarding about the lacks of reading comprehension where it will allow future researchers to develop strategies to improve the reading comprehension, achieving a social impact since the reading comprehension deficit with latent threat in the learning and achievement of each student, if there is a lack of texts understanding, teachers should provide all the support by providing timely solutions to prevent this problem. Knowing that reading capacity affects all learning areas, this problem generates different consequences such as poor academic performance. This research work allow known causes about reading comprehension deficit affecting the children and what could be the possible solutions to help and improve reading comprehension and create environment total students.